Pengaruh Prostaglandin F2Î± Terhadap Fertilitas Tikus (Rattus norvegicus) Wistar Jantan - Suripto Suripto; Lien A. Sutasurya; Hasanuddin Hasanuddin; Dwi Arinto Adi (Institut Teknologi Bandung, 2000)
The effect of PGF2Î± on the fertility of male Wistar rat (Rattus norvegicus) has been investigated . Sexually mature male rats with a body weight of 200 to 300 g were used . Sperm numbers and quality, and mating ability, were observed after rats were subcutaneously injected with 1.5 ; 2.0 and 3.0 mg/kg body weight of PGF2Î± dissolved in 0.4 ml saline solution daily for 11 consecutive days for the treatment groups , respectively. Contraction of caudal epididymis and vas defferens were recorded using myograph and physiograph, whereas the concentration of PGF2Î± was 0.4 and 0.6 mg/ml dissolved in Tyrode. The result showed that motility and number of normal as well as abnormal sperm decreased in conjuction with the increasing dosage of PGF2Î±. The contraction of organs which occurred when solution was added, showed that PGF2Î± increased the tonus tensions of caudal epididymis as well as vas deferens. There were no differences in mating ability of the treated rats compared to the control rats, while the fertility index of treated rats was significantly (p